Building a new leadership ladder transforming male-dominated organizations to support women on the rise - Geffner, Carol J. (Ascent Audio, 2024)
"When it comes to the gender gap, it is not enough to ask women to ""lean in"" and demand promotions and raises. Organizations have an obligation to level up and provide women with more opportunities for advancement. In this book, leadership and governance expert Carol Geffner makes a strong case that for women to reach their full potential, workplaces and their leaders must take a more proactive role in combating gender discrimination. Based on over 200 hours of interviews with women leaders in the United States and abroad, Building a New Leadership Ladder demonstrates that even when women are promoted to leadership positions, they are rarely given access to the same support networks as their male colleagues. Covering sectors as diverse as higher education, health care, law enforcement, and the military, the book identifies common strategies that all organizations can use to remove obstacles for women's advancement. More than a how-to guide on how women can ascend to the top, Building a New Leadership Ladder is a bold call to action for organizations and their leaders to proactively foster the conditions under which women's efforts to rise up are consistently recognized and rewarded.".
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Women executives; Career development; Sex discrimination against women; Leadership -- Psychological aspects; Organizational change; Plan de carrière; Discrimination à l'égard des femmes; Leadership; Aspect psychologique; Changement organisationnel; Audiobooks; Livres audio